The Presence and Infection Rate of Strongyloides sp. in Banteng (Bos javanicus) in Ujung Kulon National Park (UKNP) - Handayani, Handayani; Agustin, Marini; Nugraha, Arifin Budiman (-, 2025)
This study aims to identify and determine the level of Strongyloides sp. infection in buffalo (Bos javanicus javanicus) fecal samples in Ujung Kulon National Park (TNUK). The research method was conducted by examining fecal samples using native, sedimentation, and flotation methods and calculating the number of eggs per gram of feces (egg per gram, EPG) to determine the level of infection. The results showed positive Strongyloides sp. infection, indicated by the discovery of oval-shaped eggs with thin walls measuring approximately 54×41 µm. The EPG calculation yielded a value of 1600, which is categorized as a moderate infection. This level of infection indicates that the parasite's life cycle is active in the host's body and has the potential to cause mild to moderate physiological disturbances. Additionally, environmental conditions can increase the risk of reinfection, especially in wildlife habitats with high humidity levels. These findings emphasize the importance of continuous monitoring, environmental management, and parasite control measures, particularly in conservation areas such as Ujung Kulon National Park.